2009
DOI: 10.1111/j.1468-2257.2009.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a More Embedded Production System? Automotive Supply Networks and Localized Capabilities in Poland

Abstract: The article addresses the embeddedness of automotive production in Poland in terms of supply networks. A comprehensive analysis of more than 550 suppliers, supported by company interviews, shows that foreign-owned producers become embedded in Poland in the automotive supplier networks they have largely created themselves. Numerous local suppliers gain access to export markets and become integrated in a Europe-wide production system. This trend has been accompanied by significant upgrading of foreign affiliates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 26 publications
3
31
0
1
Order By: Relevance
“…Domański (2004) observes that a growing number of foreign manufacturing companies have become more embedded in Polish regions and localities, while simultaneously integrating with the global economy', as a result of some subsidiaries being transformed into 'performance' or 'quality' manufacturing plants. Recent research evidence from the CEE automotive industry points to its increasing embeddedness within the region (Domański and Gwosdz, 2009;Jürgens and Krzywdzinski, 2009). It could be also argued that the recent investments by TNCs offering outsourced or offshored business services are transforming the local milieu.…”
Section: Europementioning
confidence: 99%
“…Domański (2004) observes that a growing number of foreign manufacturing companies have become more embedded in Polish regions and localities, while simultaneously integrating with the global economy', as a result of some subsidiaries being transformed into 'performance' or 'quality' manufacturing plants. Recent research evidence from the CEE automotive industry points to its increasing embeddedness within the region (Domański and Gwosdz, 2009;Jürgens and Krzywdzinski, 2009). It could be also argued that the recent investments by TNCs offering outsourced or offshored business services are transforming the local milieu.…”
Section: Europementioning
confidence: 99%
“…The relatively high development level, high wages and organised labour of Upper Silesia makes it less vulnerable to the lock-in of low value-added specialisation; and through industrial upgrading, it can weaken the centre-periphery relationships of FDI-dominated industrial development. These relatively high-road strategies also carry some risks: the delocalisation of cost-sensitive manufacturing activities may develop into a more serious issue over time (Domański-Gwosdz 2009, Domański-Lung 2009, Gwosdz-Micek 2010, Domanski et al 2013.…”
Section: The Space-forming Effects Of the Old And New Economymentioning
confidence: 99%
“…It has evolved from an isolated and peripheral position to being a market highly integrated with the European and global production network (see Domański and Gwosdz, 2009;Winter, 2008). The main driver of change has been the activity of the Trans-National Corporations (TNCs).…”
Section: Identifying Spatial Agglomerations In the Polish Automotive mentioning
confidence: 99%
“…An extensive study on car parts manufacturers in Poland (Domański et al, 2006Domański and Gwosdz, 2009) revealed that the importance of location and distance between customers and suppliers depends on several factors. The most important are: position of the company within the supply chain, involvement in JIT or ILS supply modes, value added in production and profitability of production.…”
Section: Current Trends In the Automotive Industry And The Role Of Gementioning
confidence: 99%